(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article addresses issues of enhancing effectiveness of the process of correcting of musculoskeletal disorders (MSD), in particular, children’s posture through pedagogical means and methods of physical education used in joint actions of family members and coaches. 51 The analysis of literature sources shows that the problem raised requires finding of more effective ways for solving the touched issue, since the state of MSD of the younger generation in many countries is not at the proper level. Armenian schoolchildren are no exception in this regard, since according to YSMU, diseases of the musculoskeletal system of children are among the first in the number of functional disorders. One of the ways to effectively solve this problem is to combine joint efforts of an orthopaedist, parents of children with MSD and swimming coaches. To solve this problem, it became necessary to implement a number of measures aimed at improving the level of theoretical and methodological readiness, skills of parents and coaches to correct posture disorders. For this purpose, as part of a pedagogical experiment, seminars on the correction of posture disorders were held. Parents were presented with programs of physical therapy classes at home, and coaches were presented with sets of exercises for therapeutic swimming aimed at posture correction. The developed programs were tested in a six-month pedagogical experiment carried out both at home and in the pool with 10 children aged 11-12 years with posture disorders. With 10 children of a control group of the same age with similar MSD, only swimming sessions in accordance with established practices were held, without taking into account the doctor’s diagnosis and number of methodological recommendations reflected in the scientific and methodological literature. Analysis of data at the end of the study did not reveal any postural disorders in children of the experimental group, while in the control group only half of them did not have any correction of postural disorders. The obtained experimental results indicate the effectiveness of joint actions of parents and swimming coaches in correcting posture disorders. To implement such cooperation it is necessary to conduct educational sessions with parents and swimming coaches aimed at correction of posture disorders within the relevant organizations.